Two new species of Pergalumna (Acari, Oribatida, Galumnidae) from Costa Rica, including a key to all species of the genus from the Neotropical region - Ermilov, Sergey G. (2014)
Two new species of oribatid mites of the genus Pergalumna (Oribatida, Galumnidae), P. elongatiporosa sp. n. and P. striatiprodorsum sp. n., are described from leaf litter of a secondary forest in Costa Rica. Pergalumna elongatiporosa sp. n. is most similar morphologically to P. horvathorum P. Balogh, 1997 and P. sura P. Balogh, 1997, however, it differs from both by the body size, body surface ornamentation and morphology of notogastral porose areas A1 and A3. Pergalumna striatiprodorsum sp. n. is most similar morphologically to P. hawaiiensis hawaiiensis (Jacot, 1934) and P. strigulata Mahunka, 1978, however, it differs from P. hawaiiensis by the length of interlamellar setae and surface ornamentation of the prodorsum; from P. strigulata by the surface of ornamentation of the notogaster, length of interlamellar setae and morphology of bothridial setae. An identification key to known species of Pergalumna from the Neotropical region is given.